Critical perspectives on addiction - Netherland, Julie (Advances in medical sociology, 2012)
Our understandings of addiction are rapidly changing. New technologies and biomedical treatments are reconfiguring addiction as a brain disease, and the concept of "addiction" is expanding to cover an ever widening array of substances and behaviours, from food to shopping. This volume looks critically at how addiction has been framed historically, how it is characterized and understood through contemporary cultural representations, how new treatments and technologies are reconfiguring addiction, and how "addiction" is being expanded beyond illicit drugs and alcohol to explain phenomena such as "excessive" eating and gambling and the exponential rise in prescription narcotic use. It also examines how medical, behavioural and punitive frameworks come together to shape and control "addicts". Featuring the work of several new, up-and-coming scholars working to deepen theoretical perspectives on addiction and its relationship to social control and deviance, this volume fills a gap in addiction studies by offering critical perspectives that interrogate and challenge traditional and/or mainstream understandings of addiction.